A randomized trial of two coverage targets for mass treatment with azithromycin for trachoma. - Sheila K West; Robin Bailey; Beatriz Munoz; Tansy Edwards; Harran Mkocha; Charlotte Gaydos; Thomas Lietman; Travis Porco; David Mabey; Thomas C Quinn (PLoS Neglected Tropical Diseases)
Background The World Health Organization recommends at least 3 annual antibiotic mass drug administrations (MDA) where the prevalence of trachoma is > 10% in children ages 1-9 years, with coverage at least at 80%. However, the additional value of higher coverage targeted at children with multiple rounds is unknown. Trial design 2 × 2 factorial community randomized, double blind, trial. Trial methods 32 communities with prevalence of trachoma ≥ 20% were randomized to: annual MDA aiming for coverage of children between 80%-90% (usual target) versus aiming for coverag e> 90% (enhanced target); and to: MDA for three years versus a rule of cessation of MDA early if the estimated prevalence of ocular C. trachomatis infection was less than 5%. The primary outcome was the community prevalence of infection with C. trachomatis at 36 months. Results Over the trial's course, no community met the MDA cessation rule, so all communities had the full 3 rounds of MDA. At 36 months, there was no significant difference in the prevalence of infection, 4.0 versus 5.4 (mean adjusted difference  = 1.4%, 95% CI  =  -1.0% to 3.8%), nor in the prevalence of trachoma, 6.1 versus 9.0 (mean adjusted difference  =  2.6%, 95% CI  =  -0.3% to 5.3%) comparing the usual target to the enhanced target group. There was no difference if analyzed using coverage as a continuous variable. Conclusion In communities that had pre-treatment prevalence of follicular trachoma of 20% or greater, there is no evidence that MDA can be stopped before 3 annual rounds, even with high coverage. Increasing coverage in children above 90% does not appear to confer additional benefit.